2005
DOI: 10.1159/000085371
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Clarithromycin in Experimental Pleural Empyema Model Fluid

Abstract: Background: The degree of penetration of clarithromycin into the pleural fluid has not been studied. Objective: To determine the degree to which clarithromycin penetrates into empyemic pleural fluid using a new rabbit model of empyema. Methods: An empyema was created via the intrapleural injection of 1 ml turpentine followed 24 h later by instillation of 5 ml (1010) Escherichia coli bacteria (ATCC 35218) into the pleural space of New Zealand white rabbits. After an empyema was verified by thoracente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…Attempts have been made using a variety of species, including mice, rats, rabbits, guinea pigs and sheep, to develop a clinically reliable model of empyema. Many models require injury to the pleura to precede pathogen instillation [15][16][17][18][19], as direct bacterial administration into the pleural space often results in their complete clearance [20] or severe sepsis [21]. Other studies have suggested that a pleural effusion is required as a substrate for bacterial growth [22,23].…”
Section: Animal Models Of Pleural Infectionmentioning
confidence: 99%
“…Attempts have been made using a variety of species, including mice, rats, rabbits, guinea pigs and sheep, to develop a clinically reliable model of empyema. Many models require injury to the pleura to precede pathogen instillation [15][16][17][18][19], as direct bacterial administration into the pleural space often results in their complete clearance [20] or severe sepsis [21]. Other studies have suggested that a pleural effusion is required as a substrate for bacterial growth [22,23].…”
Section: Animal Models Of Pleural Infectionmentioning
confidence: 99%
“…This model was used for research of pharmacological characteristics and therapeutic efficacy of gentamicin 15 . Turpentine rabbit experimental empyema model with 10 10 /mL Escherichia coli was applied for the research of clarithromycin efficacy, newer quinolones and azithromycin penetration in the empyema fluid 9,26,27 . This model was also used to study linezolid and ertapenem pharmacokinetics in parapneumonic effusions 28 .…”
Section: Discussionmentioning
confidence: 99%
“…One million bacteria caused empyema in half of all animals, but with a hundred million bacteria, all animals suffered from empyema. considering these results, we decided to take 9 times more bacteria in a single (2 mL) intrapleural inoculums (4.5 10 8 /mL) S. aureus 9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations